Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $G$ be an operator on Hilbert space $H$ such that $\ker G$ is different from $\{0\}$.

Let also $P$ be the orthogonal projection onto $\ker G$, $G_1$ the restriction of $G$ on $\ker P$ and

$G_2$ the restriction of $G$ on $\operatorname{Im} P$.

My question is: can I say that $\sigma(G) = \sigma(G_{1})\cup\sigma(G_{2})$?

share|cite|improve this question

This is a general result : if $E$ is a Banach space, $F,G$ closed subspaces of $E$ such that $E = F \oplus G$ and if $T : E \to E$ is a bounded operator which leaves invariant $F$ and $G$, then $\sigma(T) = \sigma(T_{|F}) \cup \sigma(T_{|G})$.

The proof is easy if you consider resolvant sets.

If $\lambda \in \mathbb{C}$ is such that $T - \lambda I_E$ is invertible, then it follows immediately that $T_{|F} - \lambda I_F$ is one-to-one. Then, fix $y \in F$. By assumption, there is $x \in E$ with $(T-\lambda)x = y$. Writing $x = x_F + x_G$, with $x_F \in F$ and $x_G \in G$, we have $(T - \lambda)x_F = y$. (because $y$ belongs to $F$, and the sum $F \oplus G$ is direct)

This then shows that $T_{|F} - \lambda I_F$ is invertible. The same goes for $T_{|G} - \lambda I_G$.

Reciprocally, if $T_{|F} - \lambda I_F$ and $T_{|G} - \lambda I_G$ are invertible, we can easily build an inverse for $T - \lambda I_E$.

share|cite|improve this answer
the condition of boundedness of T is it necessary. – salma Aug 20 '12 at 12:56
I'm not used with unbounded operators. Perhaps you can slighty modify my proof in order to cover the general case. I don't know. – Ahriman Aug 20 '12 at 13:03
How we can build an inverse for $T−λI_{E}$? – salma Aug 21 '12 at 16:14
Take $y \in E$, and write it as $y = y_F + y_G$. Then there are $x_F \in F$ and $x_G \in G$ with $(T-\lambda)x_F = y_F$ and the same for $G$. Consider $x = x_F + x_G$. – Ahriman Aug 21 '12 at 16:21

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.